Therapeutic targeting of the NOTCH1 and neddylation pathways in T cell acute lymphoblastic leukemia - Kalay Bertulfo; Pablo Perez-Duran; Hannah Miller; Cindy Ma; Alberto Ambesi-Impiombato; Jeremy Samon; Adam Mackey; Wen-Hsuan Wendy Lin; Adolfo A. Ferrando; Teresa Palomero (Proceedings of the National Academy of Sciences, 2025)
Gamma Secretase Inhibitors (GSIs) effectively block oncogenic Notch homolog-1 (NOTCH1), a characteristic feature of T cell acute lymphoblastic leukemias (T-ALL). However, their clinical application has been stalled by the induction of severe gastrointestinal toxicity resulting from the inhibition of NOTCH signaling in the gut, which translates into increased goblet cell differentiation. Genome-wide CRISPR loss-of-function screen in the colon cancer cell line LS174T identified the neddylation pathway as a main regulator of goblet cell differentiation upon NOTCH1 inhibition. Consistently, pharmacologic inhibition of the neddylation pathway with the small molecule inhibitor MLN4924, rescued GSI-induced differentiation in LS174T cells. Mechanistically, neddylation inhibition by MLN4924 increases the protein stability of Hairy and enhancer of split-1, a direct NOTCH1 transcriptional target and key regulator of absorptive and secretory cell fate decisions. Combined treatment with GSI and MLN4924 in a murine Notch1 -dependent model of T-ALL led to leukemia regression and improved overall survival in the absence of gut toxicity. Overall, these results support the combined targeting of the NOTCH1 and neddylation pathways for the treatment of NOTCH1-induced T-ALL.